2017
DOI: 10.11648/j.ajns.20170603.22
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Integrated Ethics Program on Nurses Knowledge and Performance at Rural Areas in Fayoum Region, Egypt

Abstract: Ethical standards offer a context for behavior assessment, and nursing principles which influence nurses' goals, and approaches with patient care. The aim of this study to evaluate the Impact of Integrated ethics program on nurses practices in health centers at rural areas in Fayoum region, Egypt. A quasi-experimental design with pre and post-test was utilized. Convenience sample were used to collect 70 nurses from three maternal and child health centers in Fayoum region. Two tools were used to collect the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
2
6
0
Order By: Relevance
“…31 Similar findings were also reported by other studies conducted by Hafez et al., 3 Belal et al. 24 and Fawzia and Mohamed 16 in Egypt, who reported that culture plays an important role in giving shape to nursing professional ethical values.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…31 Similar findings were also reported by other studies conducted by Hafez et al., 3 Belal et al. 24 and Fawzia and Mohamed 16 in Egypt, who reported that culture plays an important role in giving shape to nursing professional ethical values.…”
Section: Discussionsupporting
confidence: 83%
“…Forty items of nurses’ ethical practice were developed by researchers and based on literature reviews. 14,23–25 They were classified into nine ethical components according to nursing ethical principles 23,26 as follows: 1. Respect patient rights: Five items related to measures of maintaining patient rights to receive safe nursing care (Alpha = 0.65). 2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, utilizing evidence-based information across a variety of departments and outpatient units helps achieve and ensure patient safety and high quality of care to improve patient outcomes (Galal 2014 andOliveira et al, 2018). Garrett (2015) and Belal S.(2017) also emphasized that rural nurses have to perform routine infection control measures, promote optimal wellness, participate in the management of acute or chronic illness, assist the patient to manage the disease or disability, as well provide support in end-of-life care.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the program was effective as it influenced and increased their knowledge in professional nursing ethics that confront nurses in work place related to ethical principles such as autonomy, beneficence, veracity, justice, fidelity and confidentiality. In similar study done by Belal et al,(2017) , it was noticed that implementation of the integrated ethics program had an efficient improving nurses' knowledge, and practice regarding integrated ethics in the rural areas, with highly statically significant differences in all the tested items between pre/post program implementation. While, Aliyu et al, (2014) conducted a study about "Knowledge, attitude and practice of nursing ethics and law among nurses at Federal Medical Centre, Bida" and indicated that the participating nurses possess considerably good knowledge, attitude and practice of nursing ethics and law.…”
Section: Discussionmentioning
confidence: 72%